A phase field model for martensitic transformation coupled with the heat equation. Issue 2 (14th December 2017) - Schmidt, Simon; Dornisch, Wolfgang; Müller, Ralf
Abstract: In order to consider temperature dependency in a phase field model for martensitic transformations a temperature dependent phase separation potential is introduced. The kinematics and the energetic setup underlying the phase transformation are briefly explained. Parameters are identified using molecular dynamics (MD) simulations. The kinetics of the phase field model are in good agreement with those of the MD simulations. Further, the effect of temperature on the microstructure evolution is studied for varying initial austenite contents.